PACKAGING MODEL OF THE CREATIVE ARTS INDUSTRY BASED ON MAPPING THE ARTS OF THE NUSANTARA CULTURE AS A MULTICULTURAL BASED POLITICAL POLICY STRATEGY - Nursilah, Nursilah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This article raises the issue of the packaging model of the performing arts creative industry which is based on the mapping of the archipelago's cultural arts. This model is structured to find appropriate technology in packaging the creative industry of performing arts which is gathered from various ethnic groups in the archipelago which is expected to be used as a harmonious multicultural-based political policy strategy. In particular, the targeted target is to create creative industry products for performing arts thematically, both in the form of presenting performing arts directly on stage or packaged in video form. The research method used is the Research and Development method which is carried out in multi years for 3 years. The first year's research is exploratory to map the cultural arts of the archipelago based on the theme and presentation model. The second year of research resulted in a creative industry model for the performing arts that was compiled based on the mapping of the archipelago's cultural arts that was useful for establishing a multicultural-based political policy strategy. Meanwhile, in the third year, the performance art creative industry model was tested to determine the effectiveness of the model that had been compiled. Based on this research, it can be concluded that Indonesia's cultural diversity is a resource that can be used as capital in the creative arts industry as well as the basis for determining multicultural-based political policy strategies. Given the importance of the substance of this research, it is hoped that every element of society realizes, appreciates and manages traditional dance well so that the welfare of life increases, social harmonization is built, and political stability can be maintained.